Minimal stratigraphic evidence for coseismic coastal subsidence during 2000 yr of megathrust earthquakes at the central Cascadia subduction zone - Nelson, Alan R. (2022)
Lithology and microfossil biostratigraphy beneath the marshes of a central Oregon estuary limit geophysical models of Cascadia megathrust rupture during successive earthquakes by ruling out >0.5 m of coseismic coastal subsidence for the past 2000 yr. Although the stratigraphy in cores and outcrops includes as many as 12 peat-mud contacts, like those commonly inferred to record subsidence during megathrust earthquakes, mapping, qualitative diatom analysis, foraminiferal transfer function analysis, and 14C dating of the contacts failed to confirm that any contacts formed through subsidence during great earthquakes. Based on the youngest peat-mud contact’s distinctness, >400 m distribution, ∼0.6 m depth, and overlying probable tsunami deposit, we attribute it to the great 1700 CE Cascadia earthquake and(or) its accompanying tsunami. Minimal changes in diatom assemblages from below the contact to above its probable tsunami deposit suggest that the lower of several foraminiferal transfer function reconstructions of coseismic subsidence across the contact (0.1–0.5 m) is most accurate. The more limited stratigraphic extent and minimal changes in lithology, foraminifera, and(or) diatom assemblages across the other 11 peat-mud contacts are insufficient to distinguish them from contacts formed through small, gradual, or localized changes in tide levels during river floods, storm surges, and gradual sea-level rise. Although no data preclude any contacts from being synchronous with a megathrust earthquake, the evidence is equally consistent with all contacts recording relative sea-level changes below the ∼0.5 m detection threshold for distinguishing coseismic from nonseismic changes.